Landscape in Brazilian rurality: theoretical and methodological considerations for an applied multidisciplinary study - Claudia Ribeiro; Marlise Amália Reinehr Dal Forno; Lovois de Andrade Miguel (Confins)
Landscape is one of the useful thought categories to improve reflections about the complex and multi-dimensional current Brazilian rurality. The paper shows and discusses the main concepts and methods adopted by multidisciplinary research that deals with both themes. The main question is whether the landscape – as a dynamic process linked to agricultural activities – could be recognized by this rural population, also as common good in the place. Vila Seca and Criúva, rural districts of the town of Caxias do Sul, in Rio Grande do Sul, Brazil’s southernmost state, were empirically picked as the study area. Socio-environmental conflicts between family farming activities and urban practices have motivated this research. The results are briefly presented, employing an ethnographic approach with participant observation. Fieldwork was done during the celebration cycle of the Holy Spirit, with attention categories defined by the study of agrarian systems, in addition to empirical criteria used for detecting the notion of landscape.